Cupping: a reasonable choice for attenuating morphine withdrawal symptoms in Wistar rats - Khosravi, Parinaz; Roostayi, Mohammad M.; Manshadi, Farideh Dehghan; Khademi-Kalantari, Khosro; Hassanzadeh, Kambiz; Baghban, Alireza Akbarzadeh (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Nowadays, the sedative drugs are the main treatments to attenuate the opioid withdrawal symptoms. However, physical therapies are found a safe alternative treatment without any serious adverse effects. This study aimed to evaluate the effects of cupping treatment on the morphine withdrawal symptoms in rats. Methods: Eighty rats were divided into two main groups; treated with morphine or saline, and each group was also divided to cupping and sham cupping subgroups (with single or daily treatment). Injection of morphine and saline were done in the morphine and saline groups twice a day for nine days. On the ninth day, the naloxone was administered and the withdrawal symptoms including jumping, rearing, body grooming, abdominal writing, and wet-dog shaking were recorded for 60 minutes. Cupping or sham cupping was applied on the GV14 once before or daily after withdrawal induction in each group. Results: The results revealed that a single cupping before the withdrawal induction significantly attenuated the withdrawal symptoms in the morphine group (p<0.01).But, the daily cupping failed to decrease the withdrawal symptoms in this group. The results also indicated that the daily cupping in the saline group increased the naloxone-induced withdrawal symptoms significantly (p<0.01). Conclusions: Single session cupping before the withdrawal induction could decreased the withdrawal symptoms. This finding might be related to the modulation of GABAergic system.